Synthesis and Conformational Analysis of Sterically Congested (4R)-(−)-1-(2,4,6-Trimethylbenzenesulfonyl)-3-n-butyryl-4-tert-butyl-2-imidazolidinone: X-Ray Crystallography and Semiempirical Calculations - Ibrahim A. Al-Swaidan; Adel S. El-Azab; Amer M. Alanazi; Alaa A.-M. Abdel-Aziz (Journal of Chemistry)
The crystal structure of (4R)-(−)-1-(2,4,6-trimethylbenzenesulfonyl)-3-n-butyryl-4-tert-butyl-2-imidazolidinone (3) was determined by single-crystal X-ray diffraction. Compound 3 crystallizes in triclinic system in space group P1 (≠ 1). The crystal data are a=10.62165 Å, b=16.5321 Å, c=8.95729 Å, ∝=91.1936∘, β=93.8496∘, γ=88.0974∘, V=1568.22 Å3, Z=3, Dcalc=1.253 g/cm3, μCuKα=15.98 cm−1, F000=636.00, T=20.0°C, and R=0.037. The crystal structure confirmed the occurrence of three molecules of 3A, 3B, and 3C in which the n-butyryl moiety adopted the s-transoid conformation. Crystal structure also revealed that the conformation of 2,4,6-trimethylbenzenesulfonyl groups was in anti-position relative to tert-butyl group. The crystal packing showed that three molecules of compound 3 are stacked as a result of intermolecular π-π interactions between the phenyl ring of one molecule and the phenyl ring of the other molecule by approaching each other to an interplanar separation of 5.034 Å. Interestingly, these stacked molecules are also connected by intermolecular CH-π interaction. The conformational analysis of the s-transoid  3A, 3B, and 3C was separately performed by molecular mechanic MM+ force field. Additionally, computational investigation using semiempirical AM1 and PM3 methods was performed to find a correlation between experimental and calculated geometrical parameters. The data obtained suggest that the structural data furnished by the AM1 method is in better agreement with those experimentally determined for the above compound. It has been found that the lowest energetic conformer computed gives approximate correspondence with experimental solid state data.